How can African agriculture adapt to climate change: Mapping the South African farming sector’s vulnerability to climate change and variability: A subnational assessment - Gbetibouo, Glwadys Aymone; Ringler, Claudia (International Food Policy Research Institute, 2009)
In southern Africa, by the middle of the 21st century climate change is expected to cause temperature increases of 1–3°C, broad summer rainfall reductions of 5–10 percent, and an increase in the incidence of both droughts and floods. Consequently, climate change has significant potential to negatively affect crop production in South Africa, and in turn the well-being of the country’s farmers. This brief is based on a study that examines the level of vulnerability to climate change in South Africa’s farming sector by developing a nationwide provincial-level vulnerability profile. Particular attention is paid to the underlying socioeconomic and institutional factors that determine how farmers respond to and cope with climate hazards.